Prospecting the Future of Digital and Audiobook Applications, Summaries, and the Evolution of Distribution Patterns in the Arab and International Contexts (2025–2035) (ALAM AL-KUTUB, 2026)
The e-book, audiobook, and summaries sector is rapidly evolving across global and Arab platforms, driving the digitization of publishing and broadening access to knowledge. Estimates suggest that e-book readers in the Middle East and North Africa will reach around 60.6 million by 2030, with a penetration rate of 9.9%. In Egypt, audiobook users are expected to reach 23.8 million, and in the UAE, about 1.7 million by the same year (Statista, 2025).Reports show that the production of Arabic audiobooks reached 8,000 titles in 2021, compared to 75,000 in the U.S., while classic e-book sales grew by 14%, and digital publications rose by 50% in Egypt, Saudi Arabia, and the UAE (Sharjah24, 2022; Worldys News, 2024). According to Ali Abdel Moneim, founder of Arab Bookverse, the number of Arabic audiobooks reached 12,500 by 2025.Currently, about 25 platforms operate in this field, with downloads ranging from one million to one billion globally and regionally. These platforms face challenges such as the lack of reliable statistics, rapid technological change, and the integration of artificial intelligence to enhance efficiency and content quality.This article explores the future of digital book platforms through interviews conducted by Alam Al-Kutub magazine with seven experts and executives from leading Arab companies. Using systems analysis to examine inputs, processes, and outputs, alongside a SWOT analysis of strengths, weaknesses, opportunities, and threats, the study compares global and Arab models to forecast the digital publishing landscape from 2025 to 2035.
Keywords: E-book applications, Audiobook applications, Foreseeing the future of book applications, Economics of book applications, Societal impacts of book application.